Physical performance in masters' degree students in Exercise and Sport Sciences related to the motor learning approach. - Felice Di Domenico; Giovanni Esposito; Tiziana D'Isanto; Sara Aliberti; Gaetano Raiola (Desafio Singular, 2024)
Physical activities (PA) can be characterized by a cognitive approach or an ecological-dynamic approach. Currently, no emphasis is given in master's degree in Sport Sciences to different effects of exercise in the two different forms of delivery: prescriptive teaching, heuristic learning. The objective was to measure levels of physical performance in students and test for associations between the effects of exercise and the type of learning approach. Thirty-eight sports science students were divided into two groups according to the teaching/learning methodology used in their training: cognitive (CG) and dynamic ecological (EDG). A battery of tests was administered: squat jump (SJ), countermovement jump (CMJ), countermovement jump free arms (CMJ-FA), and stiffness test (ST). A questionnaire on daily physical activity was administered. The data collected were statistically processed. Statistically significant associations emerged between outcomes and groups (P = < .05): 37% of CGs and 26% of EDGs used motorized vehicles at least once a week; only 5% of CGs and 26% of EDGs walked daily; 100% of CGs and 79% of EDGs practiced PA continuously; CGs performed better in CMJ-FA and ST. The two approaches differ in their impact on daily, structured physical activity and performance effects.